2015
DOI: 10.1016/s2095-3119(14)60770-x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and binding analyses of Bacillus thuringiensis toxin Vip3A in Cry1Ac-resistant and -susceptible strains of Helicoverpa armigera (Hübner)

Abstract: The Bacillus thuringiensis vegetative insecticidal protein, Vip3A, represents a new family of Bt toxin and is currently applied to commercial transgenic cotton. To determine whether the Cry1Ac-resistant Helicoverpa armigera would be cross-resistant to Vip3Aa protein, insecticidal activities, proteolytic activations and binding properties of Vip3Aa toxin were investigated using Cry1Ac-susceptible (96S) and Cry1Ac-resistant H. armigera strain (Cry1Ac-R). The toxicity of Vip3Aa in Cry1Ac-R slightly reduced compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…Studies also demonstrated that the colonies resistant to Cry1A proteins, Cry2Ab proteins ( T. ni and H. armigera ) or Dipel ( O. furnacalis , H. armigera , Plodia interpunctella, and T. ni ) had no cross‐resistance to Vip3 proteins (Gomis‐cebolla et al, ; P. Wang et al, ; Tables S3, S4). Several colonies of H. armigera with resistance to either Cry1Ac or Cry2Ab were also not cross‐resistance to Vip3Aa (An et al, ; Q. Zhang, Chen, Lu, Zhang, & Liang, ; Wei, Wu, Yang, & Wu, ; Table S3). Meanwhile, lack of cross‐resistance to Vip3A proteins was found in S. Frugiperda , which showed resistance to Cry1F or Cry2Ab2 in a series of studies (Bernardi et al, ; Vélez et al, ; Yang, Kerns, Head, & Brown, ; Yang, Kerns, Head, Price, & Huang, ).…”
Section: Cross‐resistance Between Cry and Vip Toxinsmentioning
confidence: 99%
“…Studies also demonstrated that the colonies resistant to Cry1A proteins, Cry2Ab proteins ( T. ni and H. armigera ) or Dipel ( O. furnacalis , H. armigera , Plodia interpunctella, and T. ni ) had no cross‐resistance to Vip3 proteins (Gomis‐cebolla et al, ; P. Wang et al, ; Tables S3, S4). Several colonies of H. armigera with resistance to either Cry1Ac or Cry2Ab were also not cross‐resistance to Vip3Aa (An et al, ; Q. Zhang, Chen, Lu, Zhang, & Liang, ; Wei, Wu, Yang, & Wu, ; Table S3). Meanwhile, lack of cross‐resistance to Vip3A proteins was found in S. Frugiperda , which showed resistance to Cry1F or Cry2Ab2 in a series of studies (Bernardi et al, ; Vélez et al, ; Yang, Kerns, Head, & Brown, ; Yang, Kerns, Head, Price, & Huang, ).…”
Section: Cross‐resistance Between Cry and Vip Toxinsmentioning
confidence: 99%
“…A Cry1Ac-resistant H. zea population also demonstrated a lack of cross-resistance to Vip3Aa (25). A Cry1Ac-selected population of H. armigera showed 1.7-fold resistance to Vip3Aa (29). In another study, cross-resistance between Cry1Ac and Vip3Aa was low in Cry1Ac-Sel H. armigera (30).…”
Section: Discussionmentioning
confidence: 93%
“…Vip3A is well known for its wide spectrum of toxic activity to lepidopteran, especially Nuctuidae insect pests such as Helicoverpa armigera, Spodoptera frugiperda, Spodoptera exigua, but no toxic activity has been shown to Ostrinia nubilalis and Ostrinia furnacalis [21][22][23]. Vip3Aa has no structural similarity with Cry1 and Cry2 proteins and has a different mode of action [12,24,25]. Vip3Aa is therefore considered to be a good candidate co-expressed with Cry proteins in Bt crops for targeting a broad spectrum and delaying the evolution of insect resistance.…”
Section: Discussionmentioning
confidence: 99%